2018
DOI: 10.1172/jci.insight.96308
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wnt/β-catenin signaling ameliorates osteoarthritis in a murine model of experimental osteoarthritis

Abstract: Osteoarthritis (OA) is a degenerative joint disease involving both cartilage and synovium. The canonical Wnt/β-catenin pathway, which is activated in OA, is emerging as an important regulator of tissue repair and fibrosis. This study seeks to examine Wnt pathway effects on synovial fibroblasts and articular chondrocytes as well as the therapeutic effects of Wnt inhibition on OA disease severity. Mice underwent destabilization of the medial meniscus surgery and were treated by intra-articular injection with XAV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(104 citation statements)
references
References 74 publications
(96 reference statements)
4
100
0
Order By: Relevance
“…Moreover, Wnt/b‐catenin signalling inhibitor and activator were introduced to further confirm the interaction between the Rac1 and Wnt/β‐catenin pathway in rat EPCs. As shown in Figure A, real‐time PCR analysis showed that Wnt/b‐catenin signalling inhibitor XAV‐939 (10 μmol/L) could mimic the effects of NCS23766, which increased the expression of aggrecan and collagen II and decreased the expression of MMP13 and ADAMTS5 after IL‐1β stimulation, while Wnt/b‐catenin signalling activator SKL2001 (40 µmol/L) could rescue the effects of NCS23766 . And the result of immunofluorescence staining of collagen II was in accordance with the mRNA results (Figure B,C).…”
Section: Resultssupporting
confidence: 52%
“…Moreover, Wnt/b‐catenin signalling inhibitor and activator were introduced to further confirm the interaction between the Rac1 and Wnt/β‐catenin pathway in rat EPCs. As shown in Figure A, real‐time PCR analysis showed that Wnt/b‐catenin signalling inhibitor XAV‐939 (10 μmol/L) could mimic the effects of NCS23766, which increased the expression of aggrecan and collagen II and decreased the expression of MMP13 and ADAMTS5 after IL‐1β stimulation, while Wnt/b‐catenin signalling activator SKL2001 (40 µmol/L) could rescue the effects of NCS23766 . And the result of immunofluorescence staining of collagen II was in accordance with the mRNA results (Figure B,C).…”
Section: Resultssupporting
confidence: 52%
“…In generally, the Wnt/b-catenin pathway is believed to be closely related to the development of OA, and inhibition of the Wnt/b-catenin pathway is believed to slow OA progression. Lietman et al determined that the expression of b-catenin was upregulated in the destabilization of the medial meniscus model of OA and human OA synovial fibroblasts, and inhibition of the Wnt/b-catenin pathway with the b-catenin inhibitor XAV-939 was found to alleviate OA progression [41]. Hu et al also found that OA cartilage exhibited higher levels of b-catenin mRNA and protein than normal cartilage [42].…”
Section: Discussionmentioning
confidence: 99%
“…These factors are capable of linking inflammation and hypertrophy, and may account for the abnormal DNA methylation patterns observed in OA cartilage, thus leading to the loss of phenotypic stability. Importantly, genetic and pharmacological manipulation of factors that drive chondrocyte hypertrophy in OA can modify OA pathology …”
Section: Transcriptional Network Driving Articular Chondrocyte Hypermentioning
confidence: 99%
“…Importantly, genetic and pharmacological manipulation of factors that drive chondrocyte hypertrophy in OA can modify OA pathology. 52,103 The switch from the quiescent and stable cellular phenotype of articular chondrocytes to the more active hypertrophic phenotype observed in OA disease involves an overall dysregulation of transcriptional networks, including those involving SOX9 and RUNX2. 2 Studies in human OA cartilage are naturally variable, and the evaluation of the mRNA and protein levels of transcriptional regulators is influenced by disease stage and proximity to cartilage lesions.…”
Section: Transcriptional Network Driving Articular Chondrocyte Hypermentioning
confidence: 99%